Use of additional nicotine replacement therapy by participants in a five-year follow-up of a tobacco cessation trial. (June 2021) - Cunningham, John A; Kushnir, Vladyslav; Selby, Peter; Zawertailo, Laurie; Tyndale, Rachel F.; Leatherdale, Scott T.; Godinho, Alexandra; Schell, Christina
Highlights: Smokers are interest in receiving free-of-charge nicotine replacement therapy. Use of full supply of NRT associated with 30-day smoking abstinence at 5 years. Half of participants purchased NRT between the six-month and five-year follow-up. Purchase of additional NRT appears unrelated to tobacco cessation at five years. Abstract: Introduction: Using data from an extended follow-up of a randomized trial of mailed nicotine patches, the current secondary analysis explores the continued level of interest in nicotine replacement therapy (NRT) as a means to promote tobacco cessation and whether the purchase of additional NRT was related to tobacco cessation. Methods: Attempts were made to re-contact participants (N = 999) from a randomized trial of mailed nicotine patches to take part in a five-year follow-up. Those contacted were asked about their current smoking status, interest in free-of-charge NRT, and purchase of other NRT in the time since the 6-month follow-up. Results: A total of 518 participants were successfully interviewed at the five-year time point. While 43.6% of these participants purchased additional NRT, this purchase was unrelated to success at tobacco cessation or to initial group randomization (received/did not received nicotine patches at baseline). Current smokers reported continued interest in receiving free-of charge NRT (77.2% were interested). Participants in the intervention group who reported using all of the nicotine patches they received at baseline (31.8%) were more likely to report purchasing additional NRT (54.9% versus 39.1%; p  = .02) and to report not currently smoking at the five-year follow-up (46.2% versus 27.2%; p  = .006) compared to those who used some or none of the nicotine patches mailed to them. Conclusions: The present study found no consistent evidence that NRT is related to long-term success at tobacco cessation. Smokers remain interested in NRT as a means to help them quit smoking.